Halal friendly tourism: capturing the Muslim market - Ab Rahman, Suhaimi; Che Man, Yaakob; Wan Zulkifli, Wan Sahida (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
Halal friendly tourism is becoming the next important sector in the halal industry. The increasing awareness for Muslim travelers has given an impact on the development of tourism industry. Muslim travelers, who represent 23 % of the estimated 2009 world population of the 6.8 billion, are the main market for this sector. The industry players as well as the governments should steps by developing the halal friendly tourism infrastructural. Among the fundamentals of the halal friendly tourism it includes halal friendly hotel, halal foodservice and also Islamic tour packages.